Novel Polymeric Biochips for Enhanced Detection of Infectious Diseases - Hosseini, Samira; Ibrahim, Fatimah (SpringerBriefs in Forensic and Medical Bioinformatics,, 2016)
This book focuses on the creation and development of polymeric platforms (different compositions) from a specific polymer system. This system can be used as an adaptive technique for producing sensitive analytical devices, or for simple integration into existing bioanalytical tools in order to enhance the detection signal.